2002
DOI: 10.1046/j.1471-4159.2002.00794.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Amyloid peptide in regulated secretory vesicles of chromaffin cells: evidence for multiple cysteine proteolytic activities in distinct pathways for β‐secretase activity in chromaffin vesicles

Abstract: A key factor in Alzheimer's disease (AD) is the beta-secretase activity that is required for the production of beta-amyloid (Abeta) peptide from its amyloid precursor protein (APP) precursor. In this study, the majority of Abeta secretion from neuronal chromaffin cells was found to occur via the regulated secretory pathway, compared with the constitutive secretory pathway; therefore, beta-secretase activity in the regulated secretory pathway was examined for the production and secretion of Abeta in chromaffin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 79 publications
(221 reference statements)
0
92
0
Order By: Relevance
“…APP is a type I trans-membrane protein that is cleaved by secretases, resulting in secretory forms of APP that are either secreted by the constitutive (25) or, as a recent study suggests, by the regulated pathway (26). Given that APP ϩ1 consists of the first 329 N-terminal amino acids of APP and therefore contains the signal peptide moiety, we anticipated that APP ϩ1 would also be secreted by neurons and could even be detected in CSF.…”
Section: Discussionmentioning
confidence: 99%
“…APP is a type I trans-membrane protein that is cleaved by secretases, resulting in secretory forms of APP that are either secreted by the constitutive (25) or, as a recent study suggests, by the regulated pathway (26). Given that APP ϩ1 consists of the first 329 N-terminal amino acids of APP and therefore contains the signal peptide moiety, we anticipated that APP ϩ1 would also be secreted by neurons and could even be detected in CSF.…”
Section: Discussionmentioning
confidence: 99%
“…This APP species might therefore be a source of A␤ production by soluble proteases of the lysosome, i.e. ␥-secretase-independent proteases, which have been suggested by some authors (62)(63)(64). For example, cathepsin D (the major soluble protease of the lysosome) is capable of cleaving soluble APP fragments at positions 42 and 43 (but not 40) (65).…”
Section: Ps-1 App and Nicastrin Are Resident Lysosomalmentioning
confidence: 91%
“…Significantly, findings in this study showed that the endogenous ␤-secretase activity in A␤-containing regulated secretory vesicles (RSV) possesses high selectivity for cleaving the WT ␤-secretase site but does not cleave the Swedish (Swe) mutant ␤-secretase site. The RSV provide production and synthesis of a major portion of secreted A␤ (8,9). Although many previous studies of ␤-secretase have utilized substrates containing the Swe mutant ␤-secretase site (10 -14) expressed in one extended family (15), it is most relevant to study proteolytic cleavage of the WT ␤-secretase site expressed in the major portion of the AD population.…”
mentioning
confidence: 99%